Induction of pre-hospital emergency anaesthesia i-PHEA: a national survey of UK HEMS practice - Mark Hodkinson; Kurtis Poole (BMC Emergency Medicine, 2023)
Abstract Background Pre-hospital emergency anaesthesia is a critical intervention undertaken by helicopter emergency medical teams. Previous studies informed current practice for induction regimes, using a standardized approach of fentanyl, ketamine and rocuronium. There may be a trend towards post-induction hypotension attributed to the induction regime used. Several new combinations of fentanyl, ketamine and rocuronium are emerging in clinical practice. There is currently no consensus on what induction regimes should be used. Methods A semi-structured survey was distributed to the medical leads of all UK air ambulance organisations between December 2022 and February 2023. Responses that were returned within the study period were included. Exclusions included missing data, declined participation and failure to return the survey within the data collection period. The survey sought to establish provision of pre-hospital emergency anaesthesia and current induction regimes for stable, unstable and post-cardiac arrest patients. Data was extracted from Microsoft Forms into Excel. Descriptive statistics were used to analyse survey response rate, provision of PHEA and induction regimes. The survey was endorsed by the National HEMS Research and Audit Forum. Results 19 air ambulance organisations responded (response rate 86%). The majority of organisations provide over 100 pre-hospital emergency anaesthetics per annum (79%, n = 15/19). A standard combination of fentanyl, ketamine and rocuronium is used as a primary induction regime in haemodynamically stable patients by 52% of services (n = 10/19). In haemodynamically compromised patients, fentanyl was omitted or pracititioner choice emphasized by 79% of services (n = 15/19). There was variability in the dose of rocuronium from 1 mg/kg to 2 mg/kg throughout services. Conclusion There is variability in the approach to pre-hospital emergency anaesthesia. There is a growing dataset that would enable development of a registry to better understand induction regimes and the impact on patient physiology. Organisations are increasingly adopting a patient centered, practitioner choice model towards induction of anaesthesia.